2017
DOI: 10.1177/1069072717748677
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional Career Decision-Making Beliefs: A Multidimensional Model and Measure

Abstract: Dysfunctional beliefs are among the most prevalent, severe difficulties many individuals face in the process of making career decisions. The goal of the present study was to develop and test a new multidimensional measure of Dysfunctional Career Decision-Making Beliefs ( DCB). The DCB questionnaire elicits individuals’ beliefs in five aspects of career decision-making: the role of chance or fate, the criticality of the decision, the role of significant others, the role of professional help, and perceived gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 78 publications
1
54
0
1
Order By: Relevance
“…Several previous studies have reported a poor reliability estimate for this category (Gati et al, 1996(Gati et al, , 2000(Gati et al, , 2013Gati, Amir, & Landman, 2010;Sovet et al, 2015;Xu & Tracey, 2014). Hechtlinger, Levin, and Gati (2019) suggested that the low reliability of the dysfunctional beliefs score might be attributable to the heterogeneity of the Structure of Career Decision-Making Difficulties 22 items in this scale of the CDDQ. Indeed, for the Dysfunctional Career Decision-Making Beliefs questionnaire (DCB; Hechtlinger et al, 2019), which allows assessing five specific types of dysfunctional beliefs, the reliabilities of the scales were adequate (.72 to .83), considering that each scale includes three items.…”
Section: Structure Of Career Decision-making Difficulties 21mentioning
confidence: 93%
See 1 more Smart Citation
“…Several previous studies have reported a poor reliability estimate for this category (Gati et al, 1996(Gati et al, , 2000(Gati et al, , 2013Gati, Amir, & Landman, 2010;Sovet et al, 2015;Xu & Tracey, 2014). Hechtlinger, Levin, and Gati (2019) suggested that the low reliability of the dysfunctional beliefs score might be attributable to the heterogeneity of the Structure of Career Decision-Making Difficulties 22 items in this scale of the CDDQ. Indeed, for the Dysfunctional Career Decision-Making Beliefs questionnaire (DCB; Hechtlinger et al, 2019), which allows assessing five specific types of dysfunctional beliefs, the reliabilities of the scales were adequate (.72 to .83), considering that each scale includes three items.…”
Section: Structure Of Career Decision-making Difficulties 21mentioning
confidence: 93%
“…Hechtlinger, Levin, and Gati (2019) suggested that the low reliability of the dysfunctional beliefs score might be attributable to the heterogeneity of the Structure of Career Decision-Making Difficulties 22 items in this scale of the CDDQ. Indeed, for the Dysfunctional Career Decision-Making Beliefs questionnaire (DCB; Hechtlinger et al, 2019), which allows assessing five specific types of dysfunctional beliefs, the reliabilities of the scales were adequate (.72 to .83), considering that each scale includes three items. However, the intercorrelations between the five scales were lower (.10-.28 and.15-.41, in two large samples), supporting the claim that having one dysfunctional belief is often not associated with having others, and thus that a total score for dysfunctional beliefs is likely have low reliability.…”
Section: Structure Of Career Decision-making Difficulties 21mentioning
confidence: 99%
“…By the same token, some authors have applied the study of decision-making in adolescents to the vocational sphere, differentiating between males and females (Abidin et al, 2019;Hechtlinger et al, 2019;Kvasková and Almenara, 2019). In these studies, differences were found in the decision-making process variables by gender; the female sample obtained scores better than the male sample.…”
Section: Autonomymentioning
confidence: 99%
“…If career beliefs are positive, someone will be more confident in achieving career goals (Krumboltz, 1994). Conversely, negative career beliefs produce doubt (Saunders, Peterson, Sampson Jr, & Reardon, 2000) and weak commitment (Hechtlinger et al, 2019). This is confirmed by the study of Saunders et al, (2000) who found that 61% of career doubts are influenced by negative career beliefs.…”
Section: Introductionmentioning
confidence: 83%